Cortical thickness, brain metabolic activity, and in vivo amyloid deposition in asymptomatic, middle-aged offspring of patients with late-onset Alzheimer's disease - Duarte-Abritta, Bárbara (2018)
Fil: Duarte-Abritta, Bárbara. Fundación FLENI. Servicio de Psiquiatría; Argentina